External shocks and policy change in different coalition opportunity structures - Yun, Changgeun (International Review of Public Administration, 2019)
Since its introduction in the late 1980s, the Advocacy Coalition Framework (ACF) has undergone three revisions in 1993, 1998, and 2007. The 2007 revision has contributed to expanding the applicability of the ACF to policy processes in both pluralistic and nonpluralistic political systems by creating a new category of variables called the coalition opportunity structure. Using a case study of nuclear energy in South Korea, which experienced a transition of the coalition opportunity structure from authoritarian to pluralist in the late 1980s, this study explores the mediating role of coalition opportunity structures in the relationship between an external shock and policy change. The findings indicate that contrary to what the ACF predicts, external shocks are exploited by a dominant coalition to further strengthen its power in the policy process in an authoritarian structure. External shocks do not have the same effect on policy subsystems in different coalition opportunity structures, and the relationship between an external shock and policy change is not a simple stimulus-response reaction. In addition, by contrasting the effect of an external shock in an authoritarian structure with that in a pluralist structure, this study explores how an external shock can function as a pathway to policy change as the ACF predicts.
Keywords: Advocacy coalition framework; coalition opportunity structures; external shocks; Korean nuclear energy; policy change